2017
DOI: 10.1007/s40291-017-0311-y
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of Methadone Response

Abstract: The efficacy of methadone maintenance treatment (MMT) in opioid use disorder is well established but responses vary. The influence of methadone pharmacodynamics and pharmacokinetics on dose requirements and program outcomes remains controversial despite the increasing number of studies evaluating genetic influences on response to methadone treatment. Furthermore, patients require different doses (usually between 60 and 100 mg/day), and there are no clear data on a plasma concentration associated with treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 150 publications
(209 reference statements)
2
26
0
Order By: Relevance
“…In their 2018 review, Fonseca and Torrens highlighted the influence of CYP2B6 , and to some extent CYP2D6 and CYP2C19 , genetic variability on methadone pharmacokinetics . Three studies described in that review reported that the CYP2B6 gene had no influence on the methadone response. Nevertheless, the differences in the published study methods may have played a role in the variability of the results, and, thus, the results should be interpreted cautiously.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In their 2018 review, Fonseca and Torrens highlighted the influence of CYP2B6 , and to some extent CYP2D6 and CYP2C19 , genetic variability on methadone pharmacokinetics . Three studies described in that review reported that the CYP2B6 gene had no influence on the methadone response. Nevertheless, the differences in the published study methods may have played a role in the variability of the results, and, thus, the results should be interpreted cautiously.…”
Section: Discussionmentioning
confidence: 99%
“…Various in vitro and in vivo studies have shown the involvement of different cytochrome P450 (CYP) enzymes, particularly CYP2B6, in methadone metabolism, associated with the CYP2B6‐G516T genetic polymorphism and, to a lesser extent, CYP2D6, CYP3A4, and the gene encoding ATP Binding Cassette Subfamily B Member 1 ( ABCB1 , the permeability glycoprotein [P‐gp] transporter) . The influence of genetic polymorphisms on pharmacodynamic properties and treatment response has been less explored, and is not supported by much evidence . Moreover, the impact of genetic variations could be compounded by interactions between many environmental and individual factors …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such testing is likely to interrogate several genes, as a multitude of factors (Lu et al, 2003;Badiani and Robinson, 2004;Scherbaum and Specka, 2008;Valentine and Fraser, 2008;Ducci and Goldman, 2012;Kreek et al, 2012;Nielsen and Kreek, 2012;Mistry et al, 2014;Bawor et al, 2015;Curtis et al, 2017;Crist et al, 2018;Fonseca and Torrens, 2018) contribute to OUD predisposition. Several gene variations are associated with predisposition to OUD and/or OUD treatment response (Kreek et al, 2012;Bawor et al, 2015;Curtis et al, 2017;Crist et al, 2018;Fonseca and Torrens, 2018). Environmental factors also contribute to OUD (Lu et al, 2003;Badiani and Robinson, 2004;Scherbaum and Specka, 2008;Valentine and Fraser, 2008), and some environmental factors can affect the influence of genetic factors on predisposition to developing addiction (Ducci and Goldman, 2012).…”
Section: -Introductionmentioning
confidence: 99%